Women as creative people in fi ne arts according to written texts from men and women for the fi rst half of twenty century in Spain - Muñoz López, Pilar (Arenal. Revista de historia de las mujeres, 2012)
Starting with the dominant ideas about the inability of the women for the artistic creation and their deficiency of “Genius”, I made a revision of the women that have written and thought about the fine arts and the creativity of the women. In the first half of the twentieth century prevail the women that have the same current opinions in their culture and in their time but gradually appear other opinions more auspicious for the creative women. From the fine arts some artists have transmitted their difficulties, points of view and experiences.